KONDISI SOSIAL EKONOMI PETANI KOPI DI DESA GAMBER KECAMATAN SIMPANG EMPAT KABUPATEN KARO SUMATERA UTARA - Ovy Frenzi Tarigan; Agatha Ayiek Sih Sayekti; Fahmi Wiryamarta Kifli (AGRIFITIA : Journal of Agribusiness Plantation, 2021)
This study aims to determine the social and economic conditions received from coffee farmers in Gamber Village, Simpang Empat District, Karo Regency, North Sumatra. This research was conducted in June to July 2019 which was located in Gamber Village, Simpang Empat Subdistrict, Karo Regency, North Sumatra. The basic method used in this research was descriptive method. To take a sample using the Snowball Sampling method. And the number of samples in this study amounted to 30 respondents coffee farmers. The results showed that (1) Social conditions of coffee farmers in Gamber Village, Simpang Empat Subdistrict, Karo District, North Sumatra showed that in terms of the level of education of farmers the respondents were quite good with an average of recent education at high school level. The average number of family responsibilities is quite good with the results of 3 dependents, the majority of farmers are only ordinary community members. (2) The economic condition of coffee farmers in Gamber Village, Simpang Empat District, Karo Regency, North Sumatra from Coffee Farmers Enterprises generates an annual income of 9,582,334 / year. Work outside the Farming Business provides an average annual income of 14,300,000 / year. (3) Coffee Farmer Household Income in Gamber Village, Simpang Empat District, Karo Regency, North Sumatra, is an average of Rp.23,882,334 / year. In the level of welfare which includes ownership of wealth, farmers are quite prosperous because of the variables studied the ownership of wealth owned is quite good. Keywords: Coffee Farmers, Farming Business, Socio-Economy